Alice Liddell as the Beggar Maid, seen: seeing and not seeing the child in Charles Dodgson's photograph. Issue 6 (3rd July 2019) - Medhurst, Jessica
ABSTRACT: The photograph Alice Liddell as the Beggar Maid (1858) is at once ubiquitous and uncritiqued: it can be found in museums and archives across the UK and North America and has been digitally reproduced across the internet, and yet the longest critical examination of it is Simon Winchester's largely biographical study, The Alice Behind Wonderland (2011). This article turns to deconstructive close reading in order to address the seeing and not seeing in and of this famous photograph. It problematises the prior scene of photography necessary to twentieth-century critiques – beginning with Higonnet (1998) and then Winchester (2011) – to consider the theoretical implications of a critical looking at the photograph as substitute for and challenge to a photographer's seeing of a photographed child and the problems posed to this by considerations of copy and photography. The final third of the paper turns to an often-overlooked critique, Herman Rappaport's 'Disarticulations: Between the Sign and the Gaze' (1994), to explore the ways in which a psychoanalytic intervention offers an alternative reading of Carroll's photography whilst necessarily repeating the child as always available to sight.